Analisis Yuridis Kebijakan Corporate Social Responsibility (CSR) dalam Meningkatkan Kesejahteraan Masyarakat pada PT Perkebunan Nusantara IV Regional I Medan - Atika Sunarto; Yunri Matondang; Muhammad Ali Adnan (Verdict: Journal of Law Science, 2026)
This study aims to analyze the policy and implementation of Corporate Social Responsibility in improving community welfare at PT Perkebunan Nusantara IV Regional I Medan. The research method employed is empirical juridical with a descriptive-analytical approach, examining both legal aspects and implementation practices in the field. Data were obtained through interviews, documentation studies, and reviews of legislation and relevant literature. The results indicate that the Corporate Social Responsibility policy of PT Perkebunan Nusantara IV has a strong legal basis, referring to the Limited Liability Company Law, Government Regulations, and other related regulations. The implementation of the policy is carried out through Corporate Social and Environmental Responsibility (CSER) programs covering education, health, social affairs, environmental sustainability, and community economic empowerment. These programs have made a tangible contribution to improving the quality of life of surrounding communities from economic, social, and environmental perspectives. Nevertheless, the implementation still faces several obstacles, such as limited community participation in program planning, inaccurate targeting of assistance, and constraints in coordination among stakeholders. To address these challenges, greater transparency, accountability, and collaboration among the company, government, and community are required. Accordingly, it can be concluded that Corporate Social Responsibility plays an important role in improving community welfare; however, optimization in its planning and implementation is necessary to ensure greater effectiveness and sustainability.